The Effect of Brand Image, Brand Experience on Brand Loyalty with Brand Trust as a Mediation Variable (Study on Marketplace Users on Tiktok Shop) - Meirisma Putri Indriani; Jati Waskito (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to analyze the effect of Brand Experience on Brand Loyalty for Tiktokshop Marketplace Users. To analyze the effect of Brand Image on Brand Loyalty for Tiktokshop Marketplace Users. To analyze the effect of Brand Experience on Brand Trust for Tiktokshop Marketplace Users. To analyze the effect of Brand Image on Brand Trust for Tiktokshop Marketplace Users. To analyze Brand Trust on Brand Loyalty for Marketplace Users on Tiktokshop. To analyze Brand Experience, Brand Image, and Brand Trust for Marketplace Users on Tiktokshop. The population used is Tiktokshop Marketplace users who have made purchase transactions at Tiktokshop while the sample is 160 respondents with a purposive sampling technique. Data analysis using SmartPLS 3.9.9. The results of this study are that the brand experience variable has a significant positive effect on brand loyalty for Tiktok Shop Marketplace users. The brand image variable has a significant positive effect on brand loyalty for Tiktok Shop Marketplace users. The brand experience variable has a significant positive effect on brand trust for Tiktok Shop Marketplace users. The brand image variable has a significant positive effect on brand trust for Tiktok Shop Marketplace users. The brand trust variable has a significant positive effect on brand loyalty in Tiktok Shop Marketplace users. The brand trust variable acts as a mediator in the influence of brand experience on brand loyalty. The brand trust variable acts as a mediator in the influence of brand image on brand loyalty.